THE INCIDENCE OF STROKE IN RSUP DR. SARDJITO IN THE YEAR OF 2012 AND 2013 - , IZHAR BIN ISMAIL ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Stroke is a worldwide and a leading cause of adult disabilities in United Kingdom. In United Kingdom, every five minutes, there are approximately about 152,000 cases is stroke every year. In England, the incidence of stroke is 178/100,000 in men and 139/100,000 in women. In Scotland it is 202/100,000 in men and 160/100,000 in women. Stroke is a type of cerebrovascular disease due to pathologic disorder of blood vessel usually arteries in the brain. Stroke can be divide into haemorrhagic stroke and ischaemic stroke. The risk factors that can lead to stroke are hypertension, cardiac disease, diabetes, hereditary, blood lipids, cholesterol, smoking, diet or obesity, soft water, race, age and gender. The main objective of this study is to find out about the incidence of stroke in RSUP Dr. Sardjito in the year of 2012 and 2013. With this data obtained, we can use them to make the earlier prevention to decrease the incidence of stroke. Aim: To determine the incidence of stroke among the stroke patients in RSUP Dr. Sardjito. Methods: This is a non-experimental research